2019
DOI: 10.3791/59083
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Inter-subject Functional Connectivity Reveals Moment-to-Moment Brain Network Configurations Driven by Continuous or Communication Paradigms

Abstract: Task-based functional magnetic resonance imaging bears great potential to understand how our brain reacts to various types of stimulation; however, this is often achieved without considering the dynamic facet of functional processing, and analytical outputs typically account for merged influences of task-driven effects and underlying spontaneous fluctuations of brain activity. Here, we introduce a novel methodological pipeline that can go beyond these limitations: the use of a sliding-window analytical scheme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The naturalistic stimuli and intersubject correlation paradigm can be extended beyond single brain regions to estimate patterns of interregional FC that show synchronized fluctuations across individuals (intersubject functional connectivity). A growing number of studies have observed synchronized fluctuations in TVFC as participants watch a movie or listen to a story (Betzel, Byrge, Esfahlani, & Kennedy, 2019;Bolton, Jochaut, Giraud, & Van De Ville, 2019;Manning et al, 2018;Simony et al, 2016), and that these fluctuations can be reliably tied to narrative elements of the story (Betzel et al, 2019;Manning et al, 2018;Simony et al, 2016). These data provide further evidence that TVFC methods can reveal subtle fluctuations in cognitive state and suggest that variation in ongoing cognitive processes during task-free conditions can modulate the temporal structure of FC.…”
Section: Evidence That Time-varying Functional Connectivity Is Related To Ongoing Cognition and Behaviormentioning
confidence: 64%
“…The naturalistic stimuli and intersubject correlation paradigm can be extended beyond single brain regions to estimate patterns of interregional FC that show synchronized fluctuations across individuals (intersubject functional connectivity). A growing number of studies have observed synchronized fluctuations in TVFC as participants watch a movie or listen to a story (Betzel, Byrge, Esfahlani, & Kennedy, 2019;Bolton, Jochaut, Giraud, & Van De Ville, 2019;Manning et al, 2018;Simony et al, 2016), and that these fluctuations can be reliably tied to narrative elements of the story (Betzel et al, 2019;Manning et al, 2018;Simony et al, 2016). These data provide further evidence that TVFC methods can reveal subtle fluctuations in cognitive state and suggest that variation in ongoing cognitive processes during task-free conditions can modulate the temporal structure of FC.…”
Section: Evidence That Time-varying Functional Connectivity Is Related To Ongoing Cognition and Behaviormentioning
confidence: 64%
“…Recently, the dynamic inter-Subject analysis is an emerging frontier in naturalistic paradigms ( Bolton et al, 2018 , 2020 ; Yang et al, 2020 ). Dynamic ISFC tracks whole-brain functional connectivity changes over time in each sliding time window, so we can establish a relationship between movie cues and time-varying brain connectivity ( Bolton et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al further confirmed the effectiveness of the ISFC method in eliminating intrinsic neural signals on the whole-brain scale (Kim et al 2018). Moreover, research by Bolton et al on depression confirmed that the dynamic ISFC method has the potential to capture the dynamic FC of a stimulus lock shared between subjects (Bolton et al 2018(Bolton et al , 2019. The application of ISFC allows us to focus on the topological properties of dynamic FC networks induced only by naturalistic stimuli.…”
Section: Introductionmentioning
confidence: 89%